1997
DOI: 10.1212/wnl.48.2.312
|View full text |Cite
|
Sign up to set email alerts
|

A multicenter, randomized, double-blind, placebo-controlled trial of influenza immunization in multiple sclerosis

Abstract: We determined the effect of influenza vaccine in patients with relapsing/remitting MS. Considerable controversy surrounds the question of whether to administer influenza vaccines to MS patients. Prevention of a febrile viral illness is clearly desirable in MS, and previous studies suggest that immunization is safe. Despite this, many clinicians avoid vaccination because they fear precipitating an MS exacerbation. We conducted a multicenter, prospective, randomized, double-blind trial of influenza immunization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
61
0
3

Year Published

2000
2000
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(69 citation statements)
references
References 4 publications
5
61
0
3
Order By: Relevance
“…In addition, several studies demonstrated genetic polymorphism of the vitamin D-binding protein among Polish 49 and Japanese 50 patients with AITDs, whereas the CYP27B1 hydroxylase polymorphism was found to predispose to Hashimoto's thyroiditis and Graves' disease in German subjects. 51 Of note, some of these associations could not be confirmed in other studies. 52 The present study has several limitations, including the small number of patients, the heterogeneity of the study population, and lack of information on nutrition, social behavior (e.g., outdoor activity) and concomitant diseases.…”
Section: Discussionmentioning
confidence: 85%
“…In addition, several studies demonstrated genetic polymorphism of the vitamin D-binding protein among Polish 49 and Japanese 50 patients with AITDs, whereas the CYP27B1 hydroxylase polymorphism was found to predispose to Hashimoto's thyroiditis and Graves' disease in German subjects. 51 Of note, some of these associations could not be confirmed in other studies. 52 The present study has several limitations, including the small number of patients, the heterogeneity of the study population, and lack of information on nutrition, social behavior (e.g., outdoor activity) and concomitant diseases.…”
Section: Discussionmentioning
confidence: 85%
“…For example, speculation existed about hepatitis B vaccination causing or triggering relapses of multiple sclerosis (MS) based on case reports. The rate of MS in the United States is estimated at 109 cases per 100,000 persons [24], and the onset or exacerbation of disease after vaccination appears to be coincidental as the increasingly large body of epidemiological evidence reveals no increased rate of MS onset or relapse after receipt of any licensed vaccine [25][26][27]. The modified WHO criteria used in this review addressed the epidemiologic evidence for causal assessment, thus taking into account whether an event occurred at a greater rate than the background incidence.…”
Section: Discussionmentioning
confidence: 99%
“…24,28 However, these were underpowered to demonstrate rare events, nor did they document less serious events that may have prompted outpatient physician visits. Randomized controlled trials and observational studies in multiple sclerosis 29,30 and rheumatoid arthritis 31 also did not demonstrate increased risk of disease flare after immunization. The primary advantage of the current study is its large numbers of included children with IBD and its ability to assess the full spectrum of health system utilization.…”
Section: Figurementioning
confidence: 90%